Career support for university graduates on the way to their successful adaptation in the labor market - Valentina G. Ryndak; Margarita V. Kozyar; Nikita A. Shchetinin (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper analyzes the problem of the effectiveness of career support for university graduates, their position in the labor market, gender segregation, expressed in the difference in wages, the appearance of female and male professions, as well as in unequal job positions offered by employers. The authors pay special attention to the consideration of the methodology for diagnosing T. Luris interpersonal relations, namely the influence of gender characteristics both on the choice of profession and on the process of work itself. The work of leading specialists in the field of employment of university graduates, their successful adaptation in the labor market, the reasons for the problems of riskiness of the primary entry of graduates into the labor market, and the inconsistency of the educational services market and the labor market were analyzed. Statistics on the gender composition of graduates of higher educational institutions for 2021 are given. The hypothesis that the level of successful adaptation of graduates and their career support are interrelated and mutually agreed with the gender and type of interpersonal relations has been confirmed. We considered the peculiarities of career support for university graduates in the context of socio-cultural understanding of the gender role, as well as the influence of pubic stereotypes on the adaptation of university graduates in the labor market. The features of various approaches to leadership and career building, interpersonal relations are described, taking into account the male and female psyche and characteristic features of intelligence.